2018
DOI: 10.3389/fpsyt.2018.00371
|View full text |Cite
|
Sign up to set email alerts
|

Internet Game Overuse Is Associated With an Alteration of Fronto-Striatal Functional Connectivity During Reward Feedback Processing

Abstract: Internet gaming disorder is associated with abnormal reward processing in the reward circuit, which is known to interact with other brain regions during feedback learning. Kim et al. (1) observed that individuals with internet game overuse (IGO) exhibit altered behavior and neural activity for non-monetary reward, but not for monetary reward. Here, we extend our analysis of IGO to the functional connectivity of the reward network. Functional MRI data were obtained during a stimulus-response association learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…First, our behavioral results and modeling parameter findings indicate that individuals with IGD exhibit a heightened inclination towards risk-taking behaviors compared to HCs, which is consistent with previous research on risky propensity of IGD in both ambiguity decision making (Jiang, Li, Zhou, & Zhou, 2020; J. Kim & Kang, 2018) and risky decision making (Ko, Wang et al, 2017; Q. Li, Wang et al, 2020; L.…”
Section: Discussionsupporting
confidence: 91%
“…First, our behavioral results and modeling parameter findings indicate that individuals with IGD exhibit a heightened inclination towards risk-taking behaviors compared to HCs, which is consistent with previous research on risky propensity of IGD in both ambiguity decision making (Jiang, Li, Zhou, & Zhou, 2020; J. Kim & Kang, 2018) and risky decision making (Ko, Wang et al, 2017; Q. Li, Wang et al, 2020; L.…”
Section: Discussionsupporting
confidence: 91%
“…The functional coupling between dorsal ACC and VS may be involved in feedback learning. Therefore, the alterations presented by individuals with IGD may imply difficulties in representing value signals attached to action outcome relationships and, consequently, learning problems [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the striatum and prefrontal cortex are intermodulations by frontostriatal circuits (Volkow et al, 2011(Volkow et al, , 2012Saad et al, 2019). The interactions between the striatum and prefrontal cortex are especially important to investigate the underlying neural mechanism of addiction, such as smoking (Kober et al, 2010) and internet gaming disorder (Yuan K. et al, 2017;Kim and Kang, 2018). Previous studies revealed structural and functional alterations in the prefrontal cortex and caudate in individuals with BQD relative to healthy controls (Liu et al, 2016b;Sariah et al, 2019).…”
Section: Discussionmentioning
confidence: 99%